2001
DOI: 10.1080/gye.15.5.325.327
|View full text |Cite
|
Sign up to set email alerts
|

Kallmann's syndrome: pregnancy through intracytoplasmic sperm injection and complicated by gestational diabetes

Abstract: Kallmann's syndrome is characterized by hypogonadotropic hypogonadism and anosmia. Assisted reproductive techniques such as intracytoplasmic sperm injection (ICSI) may be required to treat the infertile couple with oligozoospermia. Rare complications have been described in patients with Kallmann's syndrome, but gestational diabetes has not previously been reported. A case of Kallmann's syndrome with infertility is reported. Ovulation was successfully induced by human menopausal gonadotropin therapy, but pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Therefore, ovulation induction is essential for pregnancy in these cases. In the literature, a few deliveries have been reported for women with this syndrome undergoing ovulation induction by use of pulsatile GnRH [11], recombinant LH and FSH [12], hMG [13][14][15][16], and hMG then low-dose hCG [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, ovulation induction is essential for pregnancy in these cases. In the literature, a few deliveries have been reported for women with this syndrome undergoing ovulation induction by use of pulsatile GnRH [11], recombinant LH and FSH [12], hMG [13][14][15][16], and hMG then low-dose hCG [17].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that fertilization success is improved by ICSI for cases in which fertilization failure occurred in a previous IVF cycle [18]. Only 1 delivery by use of ICSI for a woman with Kallmann syndrome has been reported [14]. Another delivery was achieved by IUI [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, 24 pregnancies in women with confirmed Kallmann's syndrome have been reported since 1970 (Table 1). 2–13 Because all women with this syndrome show hypogonadotropic hypogonadism characterized by very low LH and FSH levels, ovulation induction is required to achieve pregnancy, and various ovulation induction methods have been attempted for infertile women with this syndrome, using either hMG and hCG, pulsatile gonadotropin‐releasing hormone, by means of an infusion pump or recombinant‐FSH. The key to success in ovulation induction is the choice of suitable gonadotropins and the method used for administration.…”
Section: Commentsmentioning
confidence: 99%
“…Women with Kallmann's syndrome are unable to ovulate without ovulation induction. Some reports, however, of achieving successful pregnancies in women with Kallmann's syndrome have appeared 2–13 . A case in which a successful pregnancy was achieved by the induction of ovulation with a human menopausal gonadotropin (hMG) low‐dose step‐up protocol in an infertile woman with Kallmann's syndrome is reported.…”
Section: Introductionmentioning
confidence: 99%